HUBUNGAN ANTARUMAT BERAGAMA BERSPIRIT MULTIKULTURALISME - Fawaizul Umam (Universitas Islam Negeri (UIN) Mataram, 2016)
As a spirit, multiculturalism supposed to be an adhesive social harmony and co-existence in different cultural background of society, including religious differences. By the spirit of multiculturalism, a multicultural society would be able to coexist peacefully (peace co-existence) and establish a relationship patterns in a relational tolerance while looking at each other even in forms of disparity which is inherent in every member of society, not exception the disparity of religion and orientation diversity. Establishment of spirit of multiculturalism absolutely important in the context of inter-religious relations are often shows in many cases in face of antagonistic. So that there are at least five strategic steps to strengthen the spirit of multiculturalism in the dynamic relationships between people, namely 1) strengthening the tradition of dialogue, 2) regulation of broadcasting activities of religion, 3) reeducation through educational institutions, 4) reorientation of the role of religious institutions 5) strengthening the principle of constitutionalism well as law enforcement. In multiculturalism perspective, the five steps will lead religious communities, majority and minority, the wisdom in dealing with various truths that appear in the form of religion which is so diverse. This is an affirmation which put the spirit of multiculturalism encounter social relevance, namely the strategic value for the creation of cohesiveness in the harmony of the relationship between multicultural people.